2017
DOI: 10.3138/jvme.0116-020r
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Personality on Occupational Stress in Veterinary Surgeons

Abstract: Statistics show that veterinary surgeons are in one of the professions with the highest suicide rates. This indicates the sector has significant well-being issues, with high levels of occupational stress and burnout. Previous research has focused on environmental factors in isolation, overlooking the influence of personality. This study aimed to establish that personality is a better predictor of occupational stress than environment. UK veterinary surgeons (n=311) completed an online survey composed of three q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…These variables were selected a priori because of their potential effect on the outcome variables as suggested in the literature. 2,11,[13][14][15] By calculation of Pearson correlations (r), individual factors that were significantly (P < 0.05) related to the outcome variables were included as covariates in subsequent multiple regression analyses to control for their potential effects on job satisfaction and engagement. Nonsignificant individual factors were not included in subsequent analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These variables were selected a priori because of their potential effect on the outcome variables as suggested in the literature. 2,11,[13][14][15] By calculation of Pearson correlations (r), individual factors that were significantly (P < 0.05) related to the outcome variables were included as covariates in subsequent multiple regression analyses to control for their potential effects on job satisfaction and engagement. Nonsignificant individual factors were not included in subsequent analyses.…”
Section: Discussionmentioning
confidence: 99%
“…6 Teamwork and coworker interactions also play a role. [7][8][9][10] Although reports 2,[11][12][13][14] on burnout and occupational stress among practicing veterinarians have been published, few reports exist of measurements of job satisfaction, engagement, and teamwork among veterinary technicians. To the authors' knowledge no studies have been conducted to examine how individual qualifications such as a VTS designation relate to job-related outcomes among small animal veterinary technicians.…”
mentioning
confidence: 99%
“…Moral distress is a distinct type of occupational stress, which is an adverse reaction employees experience in response to pressures of the workplace (Dawson and Thompson 2017). It differs from, for example, overwork, troubled professional relationships or the uncomplicated distress of tending to a suffering animal, by the inclusion of a conflict with one’s values.…”
Section: What Is Moral Distress?mentioning
confidence: 99%
“…Individual personality differences may combine with environmental factors to give rise to distress. Just as the trait ‘neuroticism’ was positively correlated with general occupational stress in veterinarians (Dawson and Thompson 2017) the trait ‘perfectionism’ was found to enhance vulnerability to moral distress in response to morally challenging ‘trigger’ events (Crane and others 2015). …”
Section: What Is Moral Distress?mentioning
confidence: 99%
“…Studies of the nursing profession have found high neuroticism to be associated with emotional exhaustion [ 49 ], depersonalization [ 50 ] and secondary traumatic stress, leading to increased risk of burnout [ 51 ]. A recent survey of UK-based veterinarians found neuroticism to be more strongly associated with occupational stress in this population than environmental factors such as workload [ 52 ].…”
Section: Introductionmentioning
confidence: 99%